Do nanoparticles provide a new opportunity for diagnosis of distal airspace disease? - Löndahl J (Dove Medical Press, 2016)
Jakob Löndahl,1,2 Jonas KF Jakobsson,1,2 David M Broday,3 H Laura Aaltonen,4 Per Wollmer4 1Division of Ergonomics and Aerosol Technology (EAT), Department of Design Sciences, 2NanoLund, Lund University, Lund, Sweden; 3Faculty of Civil and Environmental Engineering, Technion, Haifa, Israel; 4Department of Translational Medicine, Lund University, Malmö, Sweden Abstract: There is a need for efficient techniques to assess abnormalities in the peripheral regions of the lungs, for example, for diagnosis of pulmonary emphysema. Considerable scientific efforts have been directed toward measuring lung morphology by studying recovery of inhaled micron-sized aerosol particles (0.4–1.5 µm). In contrast, it is suggested that the recovery of inhaled airborne nanoparticles may be more useful for diagnosis. The objective of this work is to provide a theoretical background for the use of nanoparticles in measuring lung morphology and to assess their applicability based on a review of the literature. Using nanoparticles for studying distal airspace dimensions is shown to have several advantages over other aerosol-based methods. 1) Nanoparticles deposit almost exclusively by diffusion, which allows a simpler breathing maneuver with minor artifacts from particle losses in the oropharyngeal and upper airways. 2) A higher breathing flow rate can be utilized, making it possible to rapidly inhale from residual volume to total lung capacity (TLC), thereby eliminating the need to determine the TLC before measurement. 3) Recent studies indicate better penetration of nanoparticles than micron-sized particles into poorly ventilated and diseased regions of the lungs; thus, a stronger signal from the abnormal parts is expected. 4) Changes in airspace dimensions have a larger impact on the recovery of nanoparticles. Compared to current diagnostic techniques with high specificity for morphometric changes of the lungs, computed tomography and magnetic resonance imaging with hyperpolarized gases, an aerosol-based method is likely to be less time consuming, considerably cheaper, simpler to use, and easier to interpret (providing a single value rather than an image that has to be analyzed). Compared to diagnosis by carbon monoxide (DL,CO), the uptake of nanoparticles in the lung is not affected by blood flow, hemoglobin concentration or alterations of the alveolar membranes, but relies only on lung morphology. Keywords: nanoaerosols, lung particle interaction, emphysema, respiratory diagnosis, AiDA, COPD